Kearifan Lokal Masyarakat Dalam Menjaga Kelestarian Hutan Dan Mengelola Mata Air Di Desa Watowara, Kecamatan Titehena Kabupaten Flores Timur Nusa Tenggara Timur - Angin, Ignasius Suban; Sunimbar, Sunimbar (Pendidikan Geografi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2020)
Learning media is one of the supporting components of learning. Learning media has the benefit of increasing students 'interest and interactive, besides that learning media also influences students' interest in learning. The media used should follow the current development of science and technology. This research aims to (1) produce infographic poster learning media, (2) determine the feasibility of infographic poster-based learning media. The making of this infographic poster learning media uses the Borg & Gall development model which consists of ten manufacturing steps. Making this learning media using a support application, namely CANVA. The development of this learning media produces a product that is an infographic poster. Based on the results of media development,infographic media is appropriate to be used a geography based learning media; (a) The results of the validation of the material experts get a percentage of eligibility 73% with eligibility criteria, (b) The results of the validation of media experts get a percentage of eligibility 98.18% with very decent criteria, (c) The results of the user trial (teacher + student) get a percentage of feasibility 83.16% with very decent criteria. Based on the results of the validation of material and media experts as well as the results of user trials it can be concluded that the infographic poster learning media is feasible to be used as a medium for learning geography.